2017
DOI: 10.1007/s00431-017-2875-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-metabolic risk factors in youth with classical 21-hydroxylase deficiency

Abstract: Adolescents and young adults with CAH appear to have an increased risk of obesity and cardio-metabolic risk factors. Close monitoring, early identification, and secondary prevention should be implemented during pediatric care to improve the long-term health outcomes in CAH patients. What is Known: • Lifelong glucocorticoid (GC) replacement is the main treatment modality in patients with congenital adrenal hyperplasia which predispose to an adverse metabolic profile. • Adult CAH patients have adverse cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
3
25
1
Order By: Relevance
“…Therapy with glucocorticoids and androgen control influence metabolic status and outcome in all patients with CAH [ 163 166 ]. Long-term glucocorticoid replacement may cause abdominal obesity and hypertension with an onset even in youngsters [ 131 , 167 169 ]. Obesity is frequently associated with high CRP levels, hypercholesterolemia, hyperlipidemia, insulin resistance, diabetes, high leptin, and low adiponectin levels causing a common metabolic syndrome in ~20% of patients with a cardiovascular risk independent of mutations [ 79 , 123 , 167 , 170 ].…”
Section: Somatic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapy with glucocorticoids and androgen control influence metabolic status and outcome in all patients with CAH [ 163 166 ]. Long-term glucocorticoid replacement may cause abdominal obesity and hypertension with an onset even in youngsters [ 131 , 167 169 ]. Obesity is frequently associated with high CRP levels, hypercholesterolemia, hyperlipidemia, insulin resistance, diabetes, high leptin, and low adiponectin levels causing a common metabolic syndrome in ~20% of patients with a cardiovascular risk independent of mutations [ 79 , 123 , 167 , 170 ].…”
Section: Somatic Outcomesmentioning
confidence: 99%
“…Long-term glucocorticoid replacement may cause abdominal obesity and hypertension with an onset even in youngsters [ 131 , 167 169 ]. Obesity is frequently associated with high CRP levels, hypercholesterolemia, hyperlipidemia, insulin resistance, diabetes, high leptin, and low adiponectin levels causing a common metabolic syndrome in ~20% of patients with a cardiovascular risk independent of mutations [ 79 , 123 , 167 , 170 ]. Very few studies analyzed cardiovascular outcomes according to the genotype [ 111 , 123 ].…”
Section: Somatic Outcomesmentioning
confidence: 99%
“… 1 It is a group of autosomal recessive disorders that occur as a result of a mutation in the genes. 2 , 3 This interferes with the cortisol synthesis pathway and leads to decreased cortisol synthesis with or without aldosterone deficiency and increased production of adrenocorticotropic hormone through negative feedback. 2 , 4 In consequence, a hyper androgenic state with accelerated growth results in early epiphyseal closure and compromised final adult height.…”
mentioning
confidence: 99%
“…Data on the lipid levels of patients with CAH are limited. Previous studies reported lipid levels within the normal range in CAH patients, or observed no difference in lipid levels between CAH patients and healthy controls [22][23][24]. Although more favourable lipid profiles have been reported in CAH patients compared to control subjects, some studies have observed dyslipidaemia in adults with CAH [25,26].…”
Section: Discussionmentioning
confidence: 94%